Unpacking the role of Chinese EFL teacher aggression and burnout in their professional success: A teachers’ psychology perspective - Yang, Dan (Frontiers in Psychology, 2022)
This study aims to investigate the role of Chinese EFL teachers’ aggression and burnout in their professional success. To accomplish this, 362 EFL teachers (i.e., 59 Males, 303 Females) were invited to respond to three valid measures of the variables (i.e., Maslach burnout inventory, teacher aggression scale, and teacher professional success scale). Performing Spearman Rho correlation tests, negative and significant correlations were found between teacher burnout, teacher aggression and teacher professional success. Moreover, as the results of regression analyses indicated, both teacher aggression and teacher burnout were found to be the negative predictors of EFL teachers’ professional success. It implies that the higher the amount of teacher aggression and teacher burnout, the less professionally successful a teacher would be. The implications of the results are finally discussed.